An Experimental Investigation of Standard Setting in Clinical Perfectionism - Egan, Sarah; Dick, M.; Allen, Peter (Australian Academic Press Pty Ltd, 2012)
This study investigated if clinical perfectionism leads to resetting standards higher following both success and failure. A sample of 206 participants (74% female) completed an online experiment consisting of three sets of a nonverbal reasoning task and were asked before each set to select how many of the trials they aimed to get correct. Each set was followed by feedback regarding performance. Half of the participants received ‘difficult’ items for set 2, to allow investigation of failure effects. There was a significant relationship between clinical perfectionism and the standards that were set for the first set; however, there was no relationship with standard setting following success or failure. Instead, previous actual success or failure was the best predictor of goal setting. Consequently, clinical perfectionism was associated with setting higher standards in general, but not resetting standards higher following success or failure. Findings suggest that while clinical perfectionism plays a role in standard setting prior to performance, following performance actual success or failure becomes the best indicator. The implications of these findings for the cognitive behavioural model of clinical perfectionism are discussed.